If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + -2.4 = 4.4x + 2.5 Reorder the terms: -2.4 + 0.5x = 4.4x + 2.5 Reorder the terms: -2.4 + 0.5x = 2.5 + 4.4x Solving -2.4 + 0.5x = 2.5 + 4.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.4x' to each side of the equation. -2.4 + 0.5x + -4.4x = 2.5 + 4.4x + -4.4x Combine like terms: 0.5x + -4.4x = -3.9x -2.4 + -3.9x = 2.5 + 4.4x + -4.4x Combine like terms: 4.4x + -4.4x = 0.0 -2.4 + -3.9x = 2.5 + 0.0 -2.4 + -3.9x = 2.5 Add '2.4' to each side of the equation. -2.4 + 2.4 + -3.9x = 2.5 + 2.4 Combine like terms: -2.4 + 2.4 = 0.0 0.0 + -3.9x = 2.5 + 2.4 -3.9x = 2.5 + 2.4 Combine like terms: 2.5 + 2.4 = 4.9 -3.9x = 4.9 Divide each side by '-3.9'. x = -1.256410256 Simplifying x = -1.256410256
| 8x+3+4x+1=64 | | 5x+7+9x+8=141 | | (28-x)/x=8.4 | | 11x+3=2(5x-2)+7 | | 5/6x+4/3=5 | | 21z^3+28z=0 | | 4x+(3x+5)= | | -6x+x^2+3=100-10y-y^2 | | -8r+7+9r=26 | | b(2)-7r+10=0 | | 6y-(10y-3y)=2 | | 3x+2y/3x+y | | x^2+14x+y^2=-4+12y | | 28v^2+16v-44= | | 7x^2-x=7 | | x^2-21x+69=0 | | x^2+10x+87=0 | | 6(7-10x)+3(3-15x)=366 | | 15b^2+25b-40= | | -0.66666666666667x=0.83333333333333 | | -21x^2+95x+6=0 | | 9y+2(6y-5)=53 | | 2x+3c+x+c= | | r(2)-7r+10=0 | | 5x^2-18xy-8y^2= | | (3x)+(x+8)=180 | | 9y+9(14y+2)=288 | | f(x)=6x^2+13x+6 | | 2(x-1)=x-4 | | -8x+5y=7 | | x(2)-x=0 | | 2x^2+3x-7=x^2+5x+39 |